Gráfica Internete - Luis Henrique Larocca Santos (2019)
This research is a speculation around a print shop of products and services, presented from a printed publication, which appears to have been generated by a corruption of the its own website. The publication, entitled Calendar of Delays, presents a paradoxical and unstable situation, which confuses reality and representation, intention and realization. From the object, it was sought to understand how the instability generated by the images creates a movement that virtualizes and temporalizes its own geo-graphic space, leading the visual narrative of the Calendar, and consequently the reader, towards the resolution of its own paradox. The work builds the print shop while uncovers its gaps.